Resistive interchange mode destabilized by helically trapped energetic ions and its effects on energetic ions and bulk plasma in a helical plasma. (25th November 2015) - Du, X.D.; Toi, K.; Ohdachi, S.; Osakabe, M.; Ido, T.; Tanaka, K.; Yokoyama, M.; Yoshinuma, M.; Ogawa, K.; Watanabe, K.Y.; Akiyama, T.; Isobe, M.; et al.
Abstract: A resistive interchange mode of the structure (, : poloidal and toroidal mode numbers, respectively) with a bursting character and rapid frequency chirping in the range less than 10 kHz is observed for the first time in the edge region of the net current-free, low beta LHD (Large Helical Device) plasmas during high power injection of perpendicular neutral beams. The mode resonates with the precession motion of helically trapped energetic ions (EPs), following the resonant condition. The radial mode structure is recognized to be similar to that of the pressure-driven resistive interchange mode, of which radial displacement eigenfunction quite localizes around the mode rational surface, and evolves into an odd-type (or island-type) during the late of frequency chirping phase. This beam driven mode is excited when the beta value of helically trapped EPs exceeds a certain threshold. This instability is thought to be a new branch of resistive interchange mode destabilized by the trapped energetic ions. The radial transport, i.e. redistribution and losses, of helically trapped energetic ions induced by the mode transiently generates significant radial electric field near the plasma peripheral region. The large shear of thus generated radial electric field is thought to contribute to the observed suppression of micro-turbulence and transient increases of the temperature of fully ionized carbon impurity ions and electron density, suggesting improvement of bulk plasma confinement.